2022
DOI: 10.1093/mr/roac058
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound and FDG-PET/CT to detect extracranial artery involvement in patients with suspected large vessel vasculitis

Abstract: Objective To assess the accuracy of ultrasound (US) versus FDG-PET/CT to identify extracranial involvement in suspected large vessel vasculitis (LVV) patients. Methods Retrospective observational study of patients referred to our US fast track clinic with suspected LVV. All patients underwent US exam within 24 hours per protocol. FDG-PET/CT was performed according to clinician criteria. The gold standard for LVV diagnosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Nowadays, vascular imaging modalities have increasingly been incorporated into patient assessments; indeed, in more than half of suspected GCA cases showing LV-GCA. [3][4][5][6] Moreover, EULAR recommendations place ultrasound (US) of temporal (TA) and axillary arteries as first-line imaging tests and a non-compressible halo sign may replace the need for TAB in patients with high pretest probability. 7 Newer randomised controlled trials have applied additional inclusion criteria for patients with GCA such as polymyalgia rheumatica, C reactive protein (CRP) or imaging (US, fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT, MRI or CT) [8][9][10][11] and TAB has been replaced by imaging as the first-line diagnostic test in patients with suspected GCA in clinical practice.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…Nowadays, vascular imaging modalities have increasingly been incorporated into patient assessments; indeed, in more than half of suspected GCA cases showing LV-GCA. [3][4][5][6] Moreover, EULAR recommendations place ultrasound (US) of temporal (TA) and axillary arteries as first-line imaging tests and a non-compressible halo sign may replace the need for TAB in patients with high pretest probability. 7 Newer randomised controlled trials have applied additional inclusion criteria for patients with GCA such as polymyalgia rheumatica, C reactive protein (CRP) or imaging (US, fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT, MRI or CT) [8][9][10][11] and TAB has been replaced by imaging as the first-line diagnostic test in patients with suspected GCA in clinical practice.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…Several studies have compared the ability of US and FDG-PET/CT to detect LV-GCA, showing good, but not excellent agreement between both techniques. 4 18–20 However, for most studies comparing different imaging tools, the patients included are usually investigated based on either clinical or imaging findings of LV-GCA, which could potentially lead to circularity. To our knowledge, no studies have been specifically designed to assess the added value of FDG-PET/CT in patients with GCA and positive US findings.…”
Section: Discussionmentioning
confidence: 99%
“…Romosozumab is a humanized monoclonal antibody that binds with and inhibits sclerostin through Wnt signaling, resulting in a dual effect of increasing bone formation while decreasing bone resorption [ 163 ]. In the findings of a randomized clinical pilot study, romosozumab treatment was demonstrated to be more effective than denosumab in enhancing lumbar spine BMD, potentially rendering it a viable option for patients who require a significant increase in lumbar spine BMD and are at a higher risk of fractures [ 164 ]. In patients with RA, no discernible difference in disease activity or joint damage was observed between romosozumab and denosumab treatments.…”
Section: Therapeutic Agents That Affect Osteoclasts or Alleviate Infl...mentioning
confidence: 99%
“…However, there have been reports in the literature suggesting that romosozumab treatment may have adverse effects on disease activity and joint damage in RA patients. Nonetheless, it is worth noting that romosozumab treatment may not affect disease activity and joint damage in RA patients whose condition is relatively well-controlled [ 164 ].…”
Section: Therapeutic Agents That Affect Osteoclasts or Alleviate Infl...mentioning
confidence: 99%